1975
DOI: 10.1111/j.1439-0329.1975.tb00459.x
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Melampsora pinitorqua Rostr. in Italy

Abstract: Present knowledge of host range and distribution of Melampsora pinitorqua Rostr. in Italy is reported. Melampsora larici-tremulae, which occurs at high altitude in the Apennines and the Alps and infects only larch, can infect pine also in artificial conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Poplars grown under intensive management may provide favorable conditions for the development of disease epidemics and Melampsora rusts have a potentially great economic impact since they infect poplar hybrids and other tree species grown for fiber production worldwide (10,11,12,18,27,28).…”
mentioning
confidence: 99%
“…Poplars grown under intensive management may provide favorable conditions for the development of disease epidemics and Melampsora rusts have a potentially great economic impact since they infect poplar hybrids and other tree species grown for fiber production worldwide (10,11,12,18,27,28).…”
mentioning
confidence: 99%
“…The results of artificial inoculations carried out during previous experiments (LONGO et al 1970(LONGO et al , 1975) showed on the one hand that M. pinitorqua from Tuscany is able to infect besides several species of Pinus, also Larix decidua, and on the other that M. larieitremulae from the central Alps is able to infect besides Larix decidua, several species of Pinus also.…”
Section: Introductionmentioning
confidence: 93%
“…But it has been proved that lodgepole pine, at least as young plants, can be infected to a very small degree by M. pinitorqua (TROSANIN 1952;BIRAGHI, MOKIONDO 1967, Tab. 2;LONGO et al 1967LONGO et al , 1970LoNGO etal. 1975;MARTINSSON 1976).…”
Section: Mclampsora Pinitorqnamentioning
confidence: 99%